10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ObjectivesMembranous nephropathy (MN) is the leading cause of nephrotic syndrome in adults. For primary membranous nephropathy (PMN), there are few studies analyzing the clinical and pathological characteristics as well as the role of NLR (neutrophil-to-lymphocyte ratio). To explore this, we conducted this single-center, retrospective study.MethodsThis retrospective study enrolled 138 patients with PMN who were diagnosed by renal biopsy and treated at the Affiliated Hospital of Yunnan University, China, from January 2019 to November 2024. Patients were followed up for at least 12 months. Clinical and laboratory data were collected. Intergroup comparisons, survival analyses and receiver operating characteristic (ROC) curve were performed.ResultsThe results revealed that 11 patients (7.97%) in the cohort died. Patients with infection events within the first year of follow-up had higher mortality. Compared with patients without infection events within the first year, older baseline age, higher levels of blood urea nitrogen, serum creatinine, NLR, and higher incidence of ESRD were observed in both survival with infection and non-survival with infection group. The primary infection sites were the respiratory and urinary tracts. Multivariate analyses identified age as an independent predictor of infection, while age and NLR were independent predictors of mortality. The ROC curve analysis demonstrated that the NLR may serve as a predictive marker for all-cause mortality, with an AUC of 0.778 (95% CI: 0.71-0.85). The optimal cutoff value was 2.88, achieving a sensitivity of 0.91 and specificity of 0.61.ConclusionPMN patients who developed infection events within the first year after diagnosis demonstrated higher all-cause mortality. Advanced age, impaired renal function, and elevated NLR were identified as risk factors. NLR may predict mortality and serve as an accessible biomarker.